Towards entire male pigs in Europe: A perspective from the Spanish supply chain. (August 2016) - Borrisser-Pairó, F.; Kallas, Z.; Panella-Riera, N.; Avena, M.; Ibáñez, M.; Olivares, A.; Gil, J.M.; Oliver, M.A.
Abstract: In pig production, surgical castration is primarily performed to avoid boar taint and for management purposes. The European Commission plans to end surgical piglet castration voluntarily by 2018. The aim of this study was to assess the opinions and attitudes of Spanish stakeholders from the entire pork chain regarding this plan. Two methodologies were used: focus groups with 26 participants (qualitative method) were conducted with representatives of farmers, the meat industry, government institutions, retailers (including butchers), HORECA and consumers, and 127 face-to-face surveys at butchers (quantitative method) were carried out. These include an analytical hierarchical process to assess the determining factors when purchasing fresh pig meat. The results showed that a potential end of pig castration in Europe is not anticipated to affect conventional pig production in Spain. However, butchers are worried of negative effects on high quality meat and meat products, where surgical castration of pigs plays an important role. Highlights: We analysed attitudes and opinions towards piglet castration. Conventional pig production would have no problems if castration was banned. High quality production would be affected if castration was banned. A list of exceptions to European Declaration on alternatives to surgical castration of pigs should be done.